Etude Des Déterminants Du Refus De L’autopsie En Côte d’Ivoire - Okpo Nassoua Antoine (European Scientific Journal, ESJ, 2016)
This study puts in evidence the refusal determinants of autopsy in Ivory Coast. One questionnaire and interviews allowed to understand that the theory of cultural transmission exposes the influence of beliefs and values of membership group on individual and collective motivations. The ignorance of autopsy, the research disinterest of death cause and beliefs and cultural values to respect human person and body integrity are principal determinant factors of autopsy refusal in Ivory Coast.